Effect of repeated sprint exercises on cardiac autonomic recovery in adolescent and adult males: an experimental trial - De Almeida-Neto, Paulo Francisco; Alves, Julio; Gomes de Assis, Gilmara; Camara Rocha, Roberto Felipe; Silva de Oliveira, Fernanda Cristina; Medeiros da Silva, Iago; De Morais Ferreira, Ayrton Bruno; De Lima Rocha, Matheus; Aidar, Felipe J.; Moreira Silva Dantas, Paulo; Guilherme de Araujo Tinoco Cabral, Breno (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Repeated sprint exercises (RSEs) are widely used to improve physical fitness; however, their specific effects on cardiac autonomic recovery (CAR) in individuals of different ages and biological maturation (BM) stages still lack investigation. Our objective was to analyse the effect of RSE on CAR, assessed by the heart rate (HR) recovery index and the time and frequency domains of heart rate variability (HRV) in male adolescents and adults.Methods. Non-randomised experimental study. Thirty-eight individuals classified as having a high level of physical activity (males, 22 adolescents/16 adults) underwent a single session of RSE consisting of 3 rounds with 6 supra-maximal sprints interspersed with 5 minutes of passive rest. The recovery HR (between rounds) and the HRV from pre-, 20 minutes, 2 hours, and 24 hours post-RSE were assessed using short-range radio telemetry and used to calculate the CAR. In adolescents, BM was analysed using peak-height-velocity (PHV).Results. Adolescents demonstrated more efficient parasympathetic reactivation than adults after RSE ( 2p = 0.574, p < 0.05), especially those in the pre-PHV stage of BM ( 2p = 0.659, p < 0.05). For HRV, we identified an effect of time for both RSE groups on the mean square root of successive differences in intervals between heartbeats (RMSSD) ( 2p = 0.280, p < 0.05) and the low frequency/high frequency ratio (LF/HF) ( 2p = 0.129, p < 0.05). Adolescents indicated higher values than adults for RMSSD and LF.Conclusions. Parasympathetic activity is less affected in adolescents, especially pre-PHV, after RSE. In both groups, at least two hours after RSE, parasympathetic activity tended to return to baseline values, stabilising again 24 hours after RSE.
Keywords: biological maturation; heart rate variability; sports; recovery